2019
DOI: 10.1371/journal.pone.0218908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sampling frequency on fractal fluctuations during treadmill walking

Abstract: The temporal dynamics of stride-to-stride fluctuations in steady-state walking reveal important information about locomotor control and can be quantified using so-called fractal analyses, notably the detrended fluctuation analysis (DFA). Gait dynamics are often collected during treadmill walking using 3-D motion capture to identify gait events from kinematic data. The sampling frequency of motion capture systems may impact the precision of event detection and consequently impact the quantification of stride-to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is likely because non-linear measures explore the temporal structure of a time series rather than the overall magnitude of variability (e.g., SD), making them more sensitive to subtle changes occurring on a stride-by-stride basis. DFA and SE have a greater dependency on the accurate detection of gait events and are likely influenced by the disparity between the original sampling frequencies of the sensors and the force plates [ 45 ]. Liddy [ 46 ] explored the effect of the sampling rate on stride time DFA alpha and concluded that a lower sampling frequency could distort a stride time series and decrease the presence of long-term correlations.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because non-linear measures explore the temporal structure of a time series rather than the overall magnitude of variability (e.g., SD), making them more sensitive to subtle changes occurring on a stride-by-stride basis. DFA and SE have a greater dependency on the accurate detection of gait events and are likely influenced by the disparity between the original sampling frequencies of the sensors and the force plates [ 45 ]. Liddy [ 46 ] explored the effect of the sampling rate on stride time DFA alpha and concluded that a lower sampling frequency could distort a stride time series and decrease the presence of long-term correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Walking uphill or downhill is a demanding task that requires considerable effort [ 36 , 37 ], especially from people in poor physical condition. The fact that this activity is performed on a treadmill can further increase physical and psychological fatigue increasing the variability of the steps and, therefore, the temporal gait parameters calculations [ 38 , 39 ]. From a mechanical point of view, walking uphill or downhill can affect the movements of the lower limb joint to such an extent that it ultimately disrupts the normal gait phases, at least in relation to the way they are performed on a horizontal surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two devices present a different sampling frequency that can have an effect on the precision of the event detection. According to Marmelat et al [ 57 ], gait should be collected at 120 Hz for having a good compromise between accuracy and processing time. Nonetheless, this effect was not studied in this research testing different sampling frequencies due to the limitation of setting this technology at different sampling frequencies.…”
Section: Discussionmentioning
confidence: 99%